Portal Vein Thrombosis after the Consumption of Date Seed Powder: A Case Study - Mohammad Ali Zakeri; Mohammad Hossein Bagheripour; Marcello Iriti; Mahlagha Dehghan (Case Reports in Medicine)
Date seeds can be used as ingredients to enhance the nutritional value of some functional foods for human consumption as well as additives in pharmaceutical and cosmetic industries. However, there are no reports on the complications of date seeds after oral consumption. We currently report a patient with no history of gastrointestinal disease, who has been admitted to the hospital with portal vein thrombosis (PVT) and suffered from complications.